Assessment of body composition, sarcopenia and protein intake in mild to moderate Parkinson’s disease - Lima, Danielle Pessoa; Monteiro, Pauliana Alencar; Gomes de Luna, João Rafael; Viana-Júnior, Antonio Brazil; Santos, Lucas Tadeu Rocha; de Almeida, Samuel Brito; Saldanha, Rayanne Rego Ferreira; de Alencar, Madeleine Sales; Lopes, Fábia Karine de Moura; Alencar, Átila Pereira; Chaves, Raisa Carvalho de Brito Arcanjo; Brito, Wallena Cavalcante; et al. (Frontiers in Nutrition, 2025)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by motor and non motor symptoms. Nutritional status, particularly protein intake, plays a crucial role in managing PD symptoms and preventing complications such as sarcopenia. In Brazil, only 38% of the elderly frequently consume protein-rich foods. The aim of this study was to evaluate the association of protein quantity in the diet of patients with mild to moderate PD with clinical, physical, and body composition factors. A cross-sectional study was conducted involving PD patients in Hoehn and Yahr (HY) stages 1 to 3. Protein intake was assessed using dietary recall, body composition was measured using dual-energy X-ray absorptiometry (DXA), and sarcopenia was assessed following the Revised European Consensus of Sarcopenia. The mean SARC-F score was 3.97, with 51% patients screening positive for sarcopenia. The average handgrip strength was 29, 20% patients had low handgrip strength. The average Short Physical Performance Battery (SPPB) score was 8.87. Confirmed sarcopenia was present in 10% of the sample. Low protein intake (<1 g/kg/day) was observed in 35% of patients and was associated with positive screening of sarcopenia (SARC-F ≥ 4), low lean appendicular mass, and high fat mass index. We did not include patients with severe disease who exhibit more malnutrition, dysphagia, cognitive impairment, dyskinesias, and consequently more sarcopenia. We cannot, therefore, extrapolate these results to all patients with PD. Accordingly, a deeper understanding of the relationship between protein intake and body composition in PD may enhance long-term outcomes for patients.